If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + 5) + -8 = 1 Reorder the terms: 3(5 + 2x) + -8 = 1 (5 * 3 + 2x * 3) + -8 = 1 (15 + 6x) + -8 = 1 Reorder the terms: 15 + -8 + 6x = 1 Combine like terms: 15 + -8 = 7 7 + 6x = 1 Solving 7 + 6x = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 6x = 1 + -7 Combine like terms: 7 + -7 = 0 0 + 6x = 1 + -7 6x = 1 + -7 Combine like terms: 1 + -7 = -6 6x = -6 Divide each side by '6'. x = -1 Simplifying x = -1
| d-38=14 | | -(5X-4Y-7)= | | 132-r=209 | | (5/x-3)+1=(30/x^2-9) | | -4-q=-7 | | d+36=18 | | m-18=54 | | 9+d=15 | | 4-m=9 | | 3+5=2(4x+1)-7 | | 2xm=12 | | 8x-25x=8 | | 4+1/4y=-5 | | -120-5x=0 | | (3/x-1)=(5/x+2) | | 3(x+7)=19+3x | | 6(q+3)=-24 | | 7-13= | | 7t+2t=-36 | | A^2-13K-6=0 | | 5m+11=14+2m | | 9-(1+x)=2 | | 8d-7=16-3d | | (f+6)+3=7 | | 3m-7=2m-9 | | 4(4x+1)-3x-4(6-8)+8= | | -5(2r-14)=-1 | | x-4-7x=20 | | -7(8-3M)=5 | | 8=12+(x+1) | | 20-(10/(2x1)) | | y^2-5y+32=0 |